Neutrophil transendothelial migration: updates and new perspectives - Filippi, Marie-Dominique (Blood, 2019)
Neutrophils represent the first line of cellular defense against invading microorganism by rapidly moving across the blood–endothelial cell (EC) barrier and exerting effector cell functions. The neutrophil recruitment cascade to inflamed tissues involves elements of neutrophil rolling, firm adhesion, and crawling onto the EC surface before extravasating by breaching the EC barrier. The interaction between neutrophils and ECs occurs via various adhesive modules and is a critical event determining the mode of neutrophil transmigration, either at the EC junction (paracellular) or directly through the EC body (transcellular). Once thought to be a homogenous entity, new evidence clearly points to the plasticity of neutrophil functions. This review will focus on recent advances in our understanding of the mechanism of the neutrophil transmigration process. It will discuss how neutrophil–EC interactions and the subsequent mode of diapedesis, junctional or nonjunctional, can be context dependent and how this plasticity may be exploited clinically.